2021
DOI: 10.1111/jvim.16115
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bronchial narrowing in coughing dogs with heart murmurs using computed tomography

Abstract: Background: The origin of cough in dogs with heart murmurs is controversial, because the cough could be primary cardiac (eg, pulmonary edema, bronchi compression by left-sided cardiomegaly) or respiratory (eg, bronchomalacia, other bronchial or bronchiolar disease, interstitial lung disease) in origin.Hypothesis/Objectives: To study the association between left atrium (LA) dilatation and cardiomegaly and bronchial narrowing in coughing dogs with heart murmurs using computed tomography (CT).Animals: Twenty-one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…As stated above, the classic debate is whether cough in an older, small breed dog with severe left atrial enlargement caused by mitral regurgitation is a result of the enlarged left atrium compressing a normal or a malacic left caudal bronchus, caused by bronchomalacia alone, a consequence of inflammatory airway disease, or a combination of disorders. 2,6,7 Similar to the previous study, 2 the present study 1 found that numerous bronchi were collapsed. No one, however, has previously suggested that cough in these dogs is a result of compression of bronchi other than the left caudal bronchus.…”
Section: Unanticipated Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…As stated above, the classic debate is whether cough in an older, small breed dog with severe left atrial enlargement caused by mitral regurgitation is a result of the enlarged left atrium compressing a normal or a malacic left caudal bronchus, caused by bronchomalacia alone, a consequence of inflammatory airway disease, or a combination of disorders. 2,6,7 Similar to the previous study, 2 the present study 1 found that numerous bronchi were collapsed. No one, however, has previously suggested that cough in these dogs is a result of compression of bronchi other than the left caudal bronchus.…”
Section: Unanticipated Findingssupporting
confidence: 91%
“…It is difficult to understand anatomically how a large left atrium could compress bronchi other than the left caudal bronchus, especially those on the right side, which are also commonly collapsed. 1,2,8 Consequently, it seems more logical that the present study provides further evidence that many coughing dogs have widespread bronchomalacia. 8…”
Section: Unanticipated Findingsmentioning
confidence: 62%
“…Hence, the control group only included dogs without cardiovascular disease that underwent thoracic CT. Table 1 in our article presents demographic information about the dogs of the control group and statistical comparison with the group of dogs with heart disease. 4 …”
Section: Figurementioning
confidence: 99%
“…It is in especially close vicinity to the right principal (RPB), right middle (RB2), and right caudal (RB4) bronchi, which were the bronchi identified as significantly narrowed in dogs with cardiomegaly in our study. 4 Even without using IV contrast injection, the left atrium can be identified on CT, as shown in Figure 1C . In Figure 1C , it can easily be appreciated how an enlarged left atrium can compress both the left‐sided and the right‐sided bronchi.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation